Cytokine response as a biomarker for early diagnosis and outcome prediction of stem cell transplant recipients and acute leukemia patients with invasive aspergillosis. (2nd June 2022) - Puerta-Alcalde, Pedro; Ruiz-Camps, Isabel; Gudiol, Carlota; Salavert, Miquel; Barba, Pere; Morandeira, Francisco; Jarque, Isidro; Cuervo, Guillermo; Ayats, Josefina; Carratalà, Jordi; Garcia-Vidal, Carolina
Abstract: We aimed to determine the role of serum cytokine expression in invasive aspergillosis (IA) diagnosis and outcome prediction in hematologic patients. In this multicenter study, serum cytokines (IL6, IL10, INF-gamma, IL12, IL4, TNF-alpha, IL17, and IL23) were prospectively recruited from all consecutive patients with hematologic malignances at IA diagnosis and compared to control patients matched by center, age, baseline disease, and therapeutic regimen. We included 36 patients with IA and 36 controls. Serum levels of IL6 and IL10 cytokines on day 0 were significantly increased in patients with IA when compared to controls ( P  = 0.001 and P  = 0.025, respectively), even in those who were neutropenic. No differences were observed for the other cytokines. IL6 and IL10 predicted IA with an area under the ROC curve of 0.74 (95% CI 0.62–0.86) and 0.64 (95% CI 0.51–0.77), respectively. The best cutoff point in predicting IA was 20.85 pg/ml for IL6 (sensitivity 72.2%; specificity 77.8%; PPV 76.5% and NPV 73.7%), and 0.045 pg/ml for IL10 (sensitivity 62.9%; specificity 63.9%; PPV 62.9% and NPV 63.9%). IL6 levels were associated with increased mortality, with the best cutoff value being 65.59 pg/ml in mortality prediction. In conclusion, in addition to current tests in place, IL6 and IL10 levels—as measured in plasma—may help clinicians diagnose IA. High levels of IL6 at IA diagnosis are related with worse outcomes. Lay summary: We evaluated the role of serum cytokine expression in invasive aspergillosis (IA) diagnosis and outcome. Serum levels of IL6 and IL10 are increased in patients with IA compared to controls, and IL6 levels are associated with mortality.